Multi-criteria assessment to screen climate smart rice establishment techniques in coastal rice production system of India - Mohapatra, Kiran Kumar; Nayak, A. K.; Patra, R. K.; Tripathi, Rahul; Swain, Chinmaya Kumar; Moharana, K. C.; Kumar, Anjani; Shahid, Mohammad; Mohanty, Sangita; Garnaik, Saheed; Nayak, Hari Sankar; Mohapatra, Simran; et al. (Frontiers in Plant Science, 2023)
Conventional rice production technique has less economical, more vulnerable to sustainable utilization of farm resources and significantly contributed GHGs to atmosphere. In order to assess the best rice production system, six rice production techniques were evaluated, including SRI-AWD (system of rice intensification with alternate wetting and drying (AWD)), DSR-CF (direct seeded rice with continuous flooding (CF)), DSR-AWD (direct seeded rice with AWD), TPR-CF (transplanted rice with CF), TPR-AWD (transplanted rice with AWD), and FPR-CF (farmer practice with CF). The performance of these technologies was assessed using indicators such as rice productivity, energy balance, GWP, soil health, and profitability. Finally, using these indicators, a climate smart index (CSI) was calculated. Rice grown with SRI-AWD method had 54.8 % higher CSI followed by DSR-AWD and TPR-AWD over FPR-CF. Based on the CSI, it will helpful to the policymakers to implement this for cleaner and more sustainable rice production.